Microfluidic Spinning: Microfluidic‐Spinning‐Directed Microreactors Toward Generation of Multiple Nanocrystals Loaded Anisotropic Fluorescent Microfibers (Adv. Funct. Mater. 47/2015). (December 2015) - Zhang, Yan; Wang, Cai‐Feng; Chen, Li; Chen, Su; Ryan, Anthony J.
Abstract : A fiber microreactor is constructed based on a microfluidic spinning technique on page 7253 by S.Chen, A. J. Ryan, and co‐workers, for the in‐situ fabrication of nanocrystal‐loaded anisotropic fluorescent hybrid microfibers. By designing co‐axial‐flow microdevices with different geometric features, multiple nanocrystal reactions in result in microfibers with delicate bead‐shapes and Janus microstructures, capable of multiplexed optical signals. This work develops a facile platform for rapid fabrication of anisotropic fluorescent hybrid microfibers.